2021
DOI: 10.29026/oea.2021.200079
|View full text |Cite
|
Sign up to set email alerts
|

Laser scribed graphene for supercapacitors

Abstract: Supercapacitors, with the merits of both capacitors for safe and fast charge and batteries for high energy storage have drawn tremendous attention. Recently, laser scribed graphene has been increasingly studied for supercapacitor applications due to its unique properties, such as flexible fabrication, large surface area and high electrical conductivity. With the laser direct writing process, graphene can be directly fabricated and patterned as the supercapacitor electrodes. In this review, facile laser direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 135 publications
0
26
0
Order By: Relevance
“…Researchers employed reduction techniques to remove functional groups attached at specific locations (for example, plane or edge) of 2D materials aiming at changing the interlayer spacing, concentration, and structures of defects, as-oxidized degree, and other atomic interlayer or intralayer structures toward tuning electronic and photonic properties. For example, Jia et al tuned the band gap of GO films from ∼2.4 eV (pristine GO) to ∼0.1 eV (complete reduction) with laser power increase via femtosecond pulsed laser reduction (Figure d). , Guo et al precisely modulated the band gap of rGO from 2.4 to 0.9 eV by manipulating laser power ranging from 0 to 23 mW and obtained a bottom-gate GO FET with optimized on–off ratio of 56 . In addition, thermodynamic instability of 2D materials in an oxygen environment even at room temperature is inevitable, leading to surface oxidation of 2D materials.…”
Section: Preparation and Engineering Methods And The Related Property...mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers employed reduction techniques to remove functional groups attached at specific locations (for example, plane or edge) of 2D materials aiming at changing the interlayer spacing, concentration, and structures of defects, as-oxidized degree, and other atomic interlayer or intralayer structures toward tuning electronic and photonic properties. For example, Jia et al tuned the band gap of GO films from ∼2.4 eV (pristine GO) to ∼0.1 eV (complete reduction) with laser power increase via femtosecond pulsed laser reduction (Figure d). , Guo et al precisely modulated the band gap of rGO from 2.4 to 0.9 eV by manipulating laser power ranging from 0 to 23 mW and obtained a bottom-gate GO FET with optimized on–off ratio of 56 . In addition, thermodynamic instability of 2D materials in an oxygen environment even at room temperature is inevitable, leading to surface oxidation of 2D materials.…”
Section: Preparation and Engineering Methods And The Related Property...mentioning
confidence: 99%
“…For example, Jia et al tuned the band gap of GO films from ∼2.4 eV (pristine GO) to ∼0.1 eV (complete reduction) with laser power increase via femtosecond pulsed laser reduction (Figure 47d). 84,708 Guo et al precisely modulated the band gap of rGO from 2.4 to 0.9 eV by manipulating laser power ranging from 0 to 23 mW and obtained a bottom-gate GO FET with optimized on−off ratio of 56. 709 In addition, thermodynamic instability of 2D materials in an oxygen environment even at room temperature is inevitable, leading to surface oxidation of 2D materials.…”
Section: Reduction Of 2d Materialsmentioning
confidence: 99%
“…4e), which were generated by overlapping graphene sheets or crimping at the edge. [27][28][29] The high-resolution TEM image (Fig. 4f) revealed the existence of NPLIG, because the image displayed a feature with a 0.34 nm d-spacing of graphene.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 99%
“…The authors found that the lowpower laser inside the DVD was able to produce exfoliated few-layer graphene nanosheets. Recently, laser-assisted printed sensors attracted tremendous attention due to advantages, such as the low cost of production, easy sample preparation, the ability to process a range of raw materials, and their usability for different functionalities [20,21].…”
Section: Introductionmentioning
confidence: 99%